If a , b , c are the distinct roots of x 3 − 7 x 2 − 6 x + 5 = 0 ,
Find the value of ( a + b ) ( b + c ) ( a + c ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Just use the fact that - (a+b)(b+c)(c+a)=(a+b+c)(ab+bc+ca)-abc
using vieta's formular (a+b)(b+c)(a+c)=(a+b+c)(ab+bc+ac)-(abc) having known that a+b+c=7, ab+bc+ac=-6 and abc=-5. substitute in the formular to get -37
a + b + c = 7
a b + b c + c a = − 6
a b c = − 5
\((a+b)(b+c)(c+a)
= (7-c)(7-a)(7-b)\)
= 3 4 3 − 4 9 ( a + b + c ) + 7 ( a b + b c + c a ) − a b c
= 3 4 3 − 4 9 ( 7 ) + 7 ( − 6 ) − ( − 5 ) = − 3 7
You almost reached my solution. Check mine. It is a bit different at the end.
Problem Loading...
Note Loading...
Set Loading...
f ( x ) = x 3 − 7 x 2 − 6 x + 5 = ( x − a ) ( x − b ) ( x − c )
Sum of roots is 7 .
7 = a + b + c ⇒ a + b = 7 − c , b + c = 7 − a , a + c = 7 − b
⇒ ( a + b ) ( b + c ) ( a + c ) = ( 7 − a ) ( 7 − b ) ( 7 − c ) = f ( 7 ) = − 3 7